2017
DOI: 10.3748/wjg.v23.i33.6009
|View full text |Cite
|
Sign up to set email alerts
|

Helminths as an alternative therapy for intestinal diseases

Abstract: Animal models and clinical studies have shown that helminth infections exert immunomodulatory activity, altering intestinal permeability and providing a potential beneficial action on autoimmune and inflammatory disorders in human beings, such as inflammatory bowel disease (IBD) and celiac disease. This is consistent with the theory that intestinal microbiota is responsible for shaping human immunological responses. With the arrival of the immunobiologic era and the use of antibodies, we propose a distinctive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…Similar findings were published for IBS as well [166,167], thus implying B. hominis is a common constituent of healthy human microbiota exerting a protective role in gastrointestinal diseases [156]. Due to the proposed mutualistic interaction of Blastocystis and its host, some authors even suggested using the protist in a manner similar to that described for some intestinal helminths [168], in order to elicit a beneficial immunomodulatory response in patients with IBD [169]. Additional confirmation that B. hominis could be a commensal microorganism comes from a study in which patients with recurrent Clostridium difficile infections (rCDI) were treated using fecal microbiota transplantation (FMT) [170].…”
Section: Eukaryotic Parasitessupporting
confidence: 59%
“…Similar findings were published for IBS as well [166,167], thus implying B. hominis is a common constituent of healthy human microbiota exerting a protective role in gastrointestinal diseases [156]. Due to the proposed mutualistic interaction of Blastocystis and its host, some authors even suggested using the protist in a manner similar to that described for some intestinal helminths [168], in order to elicit a beneficial immunomodulatory response in patients with IBD [169]. Additional confirmation that B. hominis could be a commensal microorganism comes from a study in which patients with recurrent Clostridium difficile infections (rCDI) were treated using fecal microbiota transplantation (FMT) [170].…”
Section: Eukaryotic Parasitessupporting
confidence: 59%
“…Pioneering clinical trials showed that treatments of helminth eggs or larvae provided some clinical improvement in patients with CD and ulcerative colitis with no AEs [4,14,15]. However, a recent phase 2, randomized, placebo-controlled, multicenter trial that tested Trichuris suis ova (TSO) in patients with active CD showed that TSO efficacy was not significantly superior to placebo [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both the ES-62 glycoprotein from the filarial nematode, Acanthocheilonema vitae, and the P28 glutathione-S-transferase (P28GST) protein from schistosomes could decrease the inflammatory response (Th1 and Th17) and induce an anti-inflammatory/immuno-regulatory response (Th2/Treg). Those findings led to the concept that well-defined products derived from helminths could be used as anti-inflammatory drugs in place of the entire parasite [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these data showed polarization towards a Th2 profile with a decrease in pro-inflammatory Th1 cytokines. Currently, P28GST is being studied in CD patients in a Phase 2 clinical trial (NCT02281916) [7,33]. In order to know the local effect of P28GST, based on its enzymatic activity, we have explored the anti-inflammatory potential of a local injection of P28GST in the absence of adjuvant.…”
Section: Discussionmentioning
confidence: 99%